Peningkatan Motivasi dan Hasil Belajar Bahasa Indonesia Pada Materi Menulis Teks Cerita Pendek Melalui Model Problem Based Learning di Kelas IV MIN 2 Agam - Ratmi Wati, Feli; Rindawati, Aryani (Journal of Development Education and Learning (JODEL), 2025)
This classroom action research aimed to improve students' motivation and learning outcomes in writing short narrative texts among fourth-grade students at MIN 2 Agam. The study employed Problem Based Learning (PBL) across two cycles with 26 students. Instruments included pre/post-tests, motivation questionnaires, observation sheets, and writing rubrics. Results indicated significant improvement: mastery increased from 34.62% (mean score 62) to 92.31% (mean score 86), and high-category motivation rose from 30.77% to 88.46%. Qualitative data showed enhanced creativity, collaboration, and presentation confidence. PBL proved effective for developing narrative writing skills in primary school contexts.